Private label and macroeconomic indicators: Europe and USA - Eloy Gil-Cordero; Francisco Javier Rondán-Catalu\~na; Daniel Sigüenza-Morales (Administrative Sciences, 2020)
In this study, we have analyzed the impact and evolution of some of the most important macroeconomic indices on the market share and value of private brands. The originality and objective of this work is the linkage of macroeconomic variables in European countries and the USA with the evolution of private labels in these countries. A sample of 19 European countries and all states within the USA has been collected over a 10-year period, including data on private labels and macroeconomic indices. The analysis of the panel data has been applied using the SPSS software through the Ljung-Box test. The most significant data from the sample study is that for GDP; we advised national brand managers to make a special communication effort in nations that offer a lower GDP within Europe for their volume and in value for the US. On the other hand, it was found that when the unemployment rate increases, the value of private label market share decreases for the US, but increases for Europe, in addition to other findings that will help organizations make different business decisions.
Keywords: 350; private label; macroeconomic indexes; Europe; USA; market share